2013
DOI: 10.29268/stsc.2013.1.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Finite State Models for Quality Evaluation at Web Service Development Steps

Abstract: This paper presents a short study on evaluating the web service quality based on finite state models using the wellknown metrics of Quality of Service (QoS) and Quality of Experience (QoE). These metrics represent objective and subjective assessments. The development of any web service involves several steps and the final values of the service QoS and QoE can be essentially improved/deteriorated based on the quality reached at each development step. In this paper, five service development steps are considered:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The evaluation process helps in answering specific questions raised by decision makers and defines basic user concerns with the quality of web services. Hence, an efficient evaluation or measurement of user satisfaction or experience can mostly be achieved when taking into account both QoS and QoE of a web service (Kondratyeva et al, 2013). There are other approaches that try to address different methods for web service QoS using the algorithms to modify QoS attributes weight dynamically, automatically and objectively (Lin et al, 2014).…”
Section: Existing Qos Evaluation Approachesmentioning
confidence: 99%
“…The evaluation process helps in answering specific questions raised by decision makers and defines basic user concerns with the quality of web services. Hence, an efficient evaluation or measurement of user satisfaction or experience can mostly be achieved when taking into account both QoS and QoE of a web service (Kondratyeva et al, 2013). There are other approaches that try to address different methods for web service QoS using the algorithms to modify QoS attributes weight dynamically, automatically and objectively (Lin et al, 2014).…”
Section: Existing Qos Evaluation Approachesmentioning
confidence: 99%
“…In Kondratyeva et al [3], the authors emp techniques to perform services composition Service composition involves the aggregat service end-points (e.g., multiple web-based form a single workflow. The authors adopte composition flow patterns as shown in Figu conditional, parallel, synchronization, concurre [3] The sequential flow enables the invocatio S 1 , after service S 0 has ended.…”
Section: A Service Flow Patternsmentioning
confidence: 99%
“…The authors adopte composition flow patterns as shown in Figu conditional, parallel, synchronization, concurre [3] The sequential flow enables the invocatio S 1 , after service S 0 has ended. The conditiona service S 0 can only invoke one service betwee S k .…”
Section: A Service Flow Patternsmentioning
confidence: 99%